2010
DOI: 10.1080/14786435.2010.484659
|View full text |Cite
|
Sign up to set email alerts
|

Structural relationships among MgZn2and Mg4Zn7phases and transition structures in Mg-Zn-Y alloys

Abstract: Isothermal ageing of plastically deformed Mg-Zn-Y alloys resulted in precipitation along {1012} twin boundaries. The bulky precipitates formed had structures similar to those recently reported for the rod-like β ′ 1 precipitates, but afforded a more detailed study by high resolution TEM due to their larger size. The core of the precipitates often had the structure of monoclinic Mg 4 Zn 7 phase, and had the orientation [0001]Mg [010]; {1010}Mg (201) with either the matrix or the twin. On this Mg 4 Zn 7 phase, h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 31 publications
4
25
1
Order By: Relevance
“…The length of this unit cell A along a has shortened to about 22.3 Å. This unit is similar to that shown by Rosalie et al [23]. The other type of defect, B, shown in Figure 8c, can be described as one in which the hexagonal units along the line of fault have changed direction, and are now oriented along the fault line.…”
Section: Peak Indices Planar Spacing (å)supporting
confidence: 63%
See 2 more Smart Citations
“…The length of this unit cell A along a has shortened to about 22.3 Å. This unit is similar to that shown by Rosalie et al [23]. The other type of defect, B, shown in Figure 8c, can be described as one in which the hexagonal units along the line of fault have changed direction, and are now oriented along the fault line.…”
Section: Peak Indices Planar Spacing (å)supporting
confidence: 63%
“…An interesting question is about the stability of these structures. Similar modifications of the Mg 4 Zn 7 structure shown by us previously were tied to chemistry (local composition) [23]. In the present study, however, they seem to arise out of the lattice constraint of a periodic crystal growing on a quasiperiodic lattice.…”
Section: Structure At Planar Faultsmentioning
confidence: 44%
See 1 more Smart Citation
“…Note that the exact stoichiometry for MgZn is not known, and Mg 51 Zn 20 is not of interest as it exists over a minuscule temperature range (598-614 K). Additionally, the stoichiometry for Mg 2 Zn 3 is debated with Mg 4 Zn 7 being accepted as the best model [41,42]. We have analyzed Mg 4 Zn 7 , MgZn 2 , and Mg 2 Zn 11 in the same fashion as Mg and Zn.…”
Section: Intermetallics Of the Mg-zn Binary Systemmentioning
confidence: 99%
“…The proposed crystal structure and the orientation relationship are subsequently confirmed in separate studies on precipitates in Mg-Zn-Y alloys. [66][67][68] In these latest electron microscopy studies, it is revealed that the Mg 4 Zn 7 phase has a complex substructure and planar defects elongated along the long axis of b 0 1 rods ( Figure 5(d)). In a very recent study, [69] it was reported that the b .…”
Section: Phase Equilibria and Precipitationmentioning
confidence: 99%